First Report of Fire Blight Caused by on Korean Mountain Ash () in Korea - Yeon-Jeong Lim; Hyeonseok Oh; Mi-Hyun Lee; Eunjung Roh; Hyeonheui Ham; Dong Suk Park; Duck Hwan Park; Yong Hwan Lee (Research in Plant Disease, 2023)
During the nationwide survey of fire blight, the typical shoot blight symptoms were found on Korean mountain ash (Sorbus alnifolia) which was located near an orchard that produced fire blight on pear trees in Eumseong, Korea, May 2021. To identify the causal agent, we progressed isolation from the symptomatic leaves and shoots. Two white and mucoid colonies were isolated into the pure culture. Two isolates were identified as Erwinia amylovora according to the colony–polymerase chain reaction (PCR) with amsB primers and the phylogenetic tree using 16S rRNA sequences. To test of pathogenicity of two isolates, we inoculated immature pear fruits and understock of apple. We observed necrosis and oozes on immature pear fruits and shoot blight resulting in necrosis on apple shoots six days after inoculation. Colonies were recovered from the inoculated pears and apples, and identity was confirmed through colony PCR for amsB genes. To our knowledge, E. amylovora was first reported on Korean mountain ash native to South Korea.